Nanotechnological Approach to Increase the Antioxidant and Cytotoxic Efficacy of Crocin and Crocetin - Puglia, Carmelo; Santonocito, Debora; Musumeci, Teresa; Cardile, Venera; Graziano, Adriana Carol Eleonora; Salerno, Loredana; Raciti, Giuseppina; Crascì, Lucia; Panico, Anna Maria; Puglisi, Giovanni (Planta Medica, 2019)
Crocin and crocetin are two interesting constituents of saffron (Crocus sativus) that possess important biological activities. Their use as therapeutic agents is strongly compromised by a scarce stability, poor absorption, and low bioavailability. Therefore, to improve these unfavorable features, the aim of the present work has been to apply a nanotechnological approach based on the formulation of solid lipid nanoparticles containing crocin and crocetin. Solid lipid nanoparticles were formulated according to crocin and crocetin chemical properties, using a variation of the quasi-emulsion solvent diffusion method to formulate crocin-solid lipid nanoparticles, while crocetin-solid lipid nanoparticles were prepared following the solvent diffusion method. Morphology and dimensional distribution of solid lipid nanoparticles have been characterized by differential scanning calorimetry and photon correlation spectroscopy, respectively, while the effect of drug incorporation versus time has been studied by Turbiscan technology. In order to verify the role of the nanotechnological approach on the biological activities of crocin and crocetin, the antioxidant and antiproliferative effects of these carotenoids once incorporated in lipid nanoparticles have been evaluated. For this aim, the oxygen radical absorbance capacity assay and the MTT test were used, respectively.The results pointed out the formulation of nanometric dispersions endowed with high homogeneity and stability, with an encapsulation efficiency ranging from 80 (crocetin-solid lipid nanoparticles) to 94% (crocin-crocetin). The oxygen radical absorbance capacity assay evidenced an interesting and prolonged antioxidant activity of crocin and crocetin once encapsulated in solid lipid nanoparticles, while the nanoencapsulation strategy showed a different mechanism in ameliorating the cytotoxic effect of these two substances.
Keywords: Crocus sativus; Iridaceae; solid lipid nanoparticles; Turbiscan analysis; antioxidant; cytotoxic